Production and profitability of small scale broiler farming in selected areas of Dinajpur district, Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2021)
This study focuses on the production and profitability of the broiler farming by using Cobb-Douglas production function and Benefit-Cost analysis. For this purpose, data were collected from 50 broiler farmers living in Birol and Sadar upazila of Dinajpur district in 2020. The result revealed that involvement in broiler production seems to be profitable for the small-scale broiler farmers for the study areas notifying by net return as Tk. 6681 with a benefit-cost ratio greater than one, whereas the gross return was Tk.193367. The net return over the total cost is 0.075. The production function resulted that feed, medicines and human labor had significant positive effect on production of broiler whereas only rental cost had negative effect. Training had a highly significant (p